The business of ecosystem restoration - Comiteau, Lauren, (SAGE Business Cases., 2014)
There are some two billion hectares of severely depleted land on Earth, some 20 percent of the planet, due to decades of agro-farming, deforestation, overfishing and over-grazing. Ecologist and former IUCN NL director Willem Ferwerda wants to reclaim them a few hundred thousand hectors at a time, saying if we don't act now, the world is doomed. He has created the Ecosystem Return Foundation to match businesses with local partners in restoration projects, believing that without business involvement, it will be impossible to scale up the world's current small-time programs. He is already working in Poland, Spain and the Galapagos. And in Senegal, Ferwerda is hoping that collaboration with the Millennium Villages Project not only helps meet the Millennium Development Goals, but attracts private investors and businesses to scale-up existing successful projects in organic farming and reforestation. But restoration is a long-term investment, and Ferwerda's biggest challenge remains: How do you convince businesses to invest in projects that likely won't see a return for 20 years?